Rehabilitation of maxillary prosthodontics using removable partial denture with extracoronal attachment : Rehabilitasi prostodontik rahang atas dengan gigi tiruan sebagian lepasan dengan extracoronal attachment - Eri Hendra Jubhari; Nurhayani Safitri (Makassar Dental Journal PDGI Makassar, 2021)
Several methods are available for the management of partial tooth loss, namely by using removable partial dentures, fixed den-tures, and implants. Combined dentures can be the treatment of choice when implant or FD are not possible and can be an ade-quate alternative to conventional clasps and RPD. This article is intended to determine the maxillary prosthodontic rehabilita-tion with RPD using an extracoronal attachment. The repair of partially missing teeth is a challenge in treatment planning. The technique followed by the care of the patient is effective in providing optimal care for an individual. The use of the combined RPD and FD makes for more retentive and esthetic, stable and function in the replacement of missing teeth. Long-term suc-cess requires sophisticated laboratory techniques, clinical expertise, and depends on biological factors, especially periodontal conditions.